Prevalence of Frailty in Patients Undergoing Cardiac Valve Surgery: Comparison of Frailty Tools - Harada,Gabriela (2021)
Abstract Background There is no consensus among tools for assessing frailty. Objective To evaluate the prevalence of frailty according to different tools in patients referred for elective valve cardiac surgery. Methods This is a cross-sectional study. All patients were ≥ 18 years of age, clinically stable. The following patients were excluded: those unable to perform the tests because of physical, cognitive, or neurological limitations; those requiring non elective/emergency procedures or hemodynamic instability. During the preoperative cardiology visit, frailty was assessed by the Short Physical Performance Battery (SPPB), the Frailty Deficit Index (FDI), handgrip strength, and gait speed 3m. For the entire analysis, the statistical significance was set at 5%. Results Our cohort consisted of 258 subjects. From the total cohort, 201 were ≤ 70 years of age (77.9%), the predominant etiology according to rheumatic disease (50.7% vs 8.8%; p=0.000) with double mitral lesion (24.9% vs 0%; p=0.000). Frailty was present in 32.9% according SPPB, 29.1% with reduced muscular strength. and 8.9% with FDI. Handgrip strength was weaker in elderly patients (26.7 vs 23.6; p=0.051) and gait speed was lower in the younger group, in which 36% were considered frail (36% vs 14%; p=0.002). Variables associated with frailty were age ≥ 70 years, female gender, aortic stenosis, and regurgitation. Conclusion Frailty in adult patients who will have elective heart valve surgery is present even in the younger groups, although the older group with comorbidities are more frail. Frailty was more clearly shown by the SPPB than by the FDI and handgrip tests.